PENGARUH DISIPLIN PEGAWAI TERHADAP PELAYANAN ANGGOTA DPRD KABUPATEN KUTAI TIMUR DI KOMISI D - Muntiatun, Muntiatun (PREDIKSI, 2016)
This study aims to find the effect of employee discipline to service of legislators in the East Kutai Regency of Commission D, therefore the researchers formulated the hypothesis "Allegedly discipline has a relationship with the services to legislators of Commission D of East Kutai Regency".The timing of the research was conducted in late December 2015 to April 2016 for 4 (four) months. The research method in this study is quantitative, the data obtained through direct observation to the field, interviews and distributing questionnaires to the interviewees by the number of samples is 14 (fourteen) of respondents.Based on calculations using the product moment coefficient known to have a strong influence among the discipline with the service and the number 0.947. This figure is interpreted as a strong correlation.While testing the hypothesis generating that empirical rxy of 0.947> r xy table = 0.532. Thus the hypothesis is accepted, because there is significance (significance) between the discipline of the services to members of the East Kutai Regency in Commission D.